2016
DOI: 10.1111/1748-8583.12115
|View full text |Cite
|
Sign up to set email alerts
|

Employee ownership and firm performance: a meta‐analysis

Abstract: Employee ownership has been an area of significant practitioner and academic interest for the past four decades. Yet, empirical results on the relationship between employee ownership and firm performance remain mixed. To aggregate findings and provide potential direction for future theoretical development, we conducted a meta‐analysis of 102 samples representing 56,984 firms. Employee ownership has a small, but positive and statistically significant relation to firm performance ( truer¯ = 0.04). The effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 103 publications
5
123
0
Order By: Relevance
“…Even though there is much debate about the precise mechanisms through which these schemes impact on performance, there is strong theoretical support and empirical evidence to suggest that ESO schemes are associated with higher labor productivity (Freeman, Blasi & Kruse, 2010; Kim & Ouimet, 2014; Park & Song, 1995) and performance in organizations (Bryson & Freeman ; Blasi, Freeman, Mackin, & Kruse, 2010; Fernie & Metcalf, ; Kruse et al, 2010b; Long, ; McNabb & Whitfield, ; O’ Boyle et al, 2016; Pendleton, ; Sengupta, ; Sengupta et al, ). In a meta‐analysis of 27 studies, Kruse and Blasi (1995, p. 26, in O'Boyle et al, ) concluded that studies on employee ownership and firm productivity or profitability frequently “indicate better or unchanged performance.” A more recent meta‐analysis of 102 studies representing 56,984 firms from around the world found that employee ownership had a small but a positive and statistically significant relationship with firm performance (O'Boyle et al, ). The sample was dominated by U.S.‐based studies and pointed to the role of context in shaping the strength of ESO performance relationship.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Even though there is much debate about the precise mechanisms through which these schemes impact on performance, there is strong theoretical support and empirical evidence to suggest that ESO schemes are associated with higher labor productivity (Freeman, Blasi & Kruse, 2010; Kim & Ouimet, 2014; Park & Song, 1995) and performance in organizations (Bryson & Freeman ; Blasi, Freeman, Mackin, & Kruse, 2010; Fernie & Metcalf, ; Kruse et al, 2010b; Long, ; McNabb & Whitfield, ; O’ Boyle et al, 2016; Pendleton, ; Sengupta, ; Sengupta et al, ). In a meta‐analysis of 27 studies, Kruse and Blasi (1995, p. 26, in O'Boyle et al, ) concluded that studies on employee ownership and firm productivity or profitability frequently “indicate better or unchanged performance.” A more recent meta‐analysis of 102 studies representing 56,984 firms from around the world found that employee ownership had a small but a positive and statistically significant relationship with firm performance (O'Boyle et al, ). The sample was dominated by U.S.‐based studies and pointed to the role of context in shaping the strength of ESO performance relationship.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Moreover, studies also find that these firms have higher productivity on average (O'Boyle et al 2016). But other studies find neutral effects or even find lower levels of satisfaction and higher levels of absenteeism (Arando et al 2011;Blasi et al 2008;Keef 1998;Kruse 1984;Rhodes and Steers 1981).…”
Section: Introductionmentioning
confidence: 96%
“…Preference for some schemes depends on country-level factors. Some schemes are more related to possibility improved labour productivity and performance (Blasi et al, 2010a;O'Boyle et al, 2016;Bryson & Freeman, 2010). Among various schemes, share ownership has the clearest positive association with productivity, but its impact is the largest when firms combine it with other forms of participation (Bryson & Freeman, 2010;Poutsma & Braam, 2012).…”
Section: Concept Of Employee Financial Participation and Core Issuesmentioning
confidence: 99%
“…Ongoing control in decisionmaking and entrepreneurial co-determination are strong arguments for taking one of employee financial participation schemes. They could be reinforced by other economic arguments, such as enhancement of motivation and productivity (O'Boyle, 2016;Lowitzsch, 2009a).…”
Section: Introductionmentioning
confidence: 99%